2009
DOI: 10.1137/07068610x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Waves in Long Range Random Media

Abstract: Abstract. We consider waves propagating through multiscale media. Much is known about waves propagating through a medium that satisfies a scale separation assumption with random fluctuations on a microscale. Here we go beyond this situation and consider waves propagating through a medium defined in terms of a long range process. Such a medium can, for instance, be modeled in terms of a one-dimensional fractional Brownian motion with variations on a continuum of scales. Fractal medium models are used to model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…Thus, the slow decay of correlations leads to time-separation of the energy and phase evolutions, a phenomenon we plan to address in detail elsewhere. Let us mention that to the best of our knowledge the first study of wave propagation in random media with slowly decaying correlations was done in the onedimensional case [12,20], where it was shown that a pulse going through a random medium with long range correlations performs a fractional Brownian motion around its mean position, as opposed to the regular Brownian motion in the rapidly decorrelating case [11]. On the other hand, motion of particles in such random media leading to fractional Brownian limits was considered in [10,17,18].…”
Section: Upon a Change Of Variablesmentioning
confidence: 99%
“…Thus, the slow decay of correlations leads to time-separation of the energy and phase evolutions, a phenomenon we plan to address in detail elsewhere. Let us mention that to the best of our knowledge the first study of wave propagation in random media with slowly decaying correlations was done in the onedimensional case [12,20], where it was shown that a pulse going through a random medium with long range correlations performs a fractional Brownian motion around its mean position, as opposed to the regular Brownian motion in the rapidly decorrelating case [11]. On the other hand, motion of particles in such random media leading to fractional Brownian limits was considered in [10,17,18].…”
Section: Upon a Change Of Variablesmentioning
confidence: 99%
“…Wave propagation in multiscale and rough media, with longrange fluctuations, has recently attracted a lot of attention, as more and more data collected in real environments confirm that this situation can be encountered in many different contexts, such as in geophysics [11] or in laser beam propagation through the atmosphere [13,16,25]. Recently it has been shown that the main effect of such fluctuations of the medium parameters is a random time shift for the wave front, that obeys a Gaussian statistics described in terms of a fractional Brownian motion [22]. Here we observe the wave front along its random characteristics and we show that the wave front also experiences a deterministic shape modification, that can be described in terms of a pseudo-differential operator that depends on the power decay rate of the autocorrelation function of the fluctuations of the medium parameters.…”
mentioning
confidence: 99%
“…These results are derived in [14]. Related results for particular situations, respectively paraxial propagation, strongly heterogeneous media with long-range correlations and Goupillaud media can be found in [10,21,29]. In [28] the transmitted pulse in so called locally layered media was considered and it was shown that central results on the pulse deformation are robust with respect to such medium perturbations, while in [13] solitons in random media with long range perturbations was considered and it was shown that aspects of the pulse deformation theory that predicts power law rather than exponential decay generalizes to nonlinear situations.…”
Section: Introductionmentioning
confidence: 69%